THE USE OF SOCIAL MEDIA PLATFORMS IN ENGLISH AS A FOREIGN LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The increasing use of digital technologies has transformed many aspects of education, including the teaching and learning of English as a Foreign Language (EFL). Social media platforms have emerged as valuable tools that facilitate communication, collaboration, and access to authentic language materials. Unlike traditional classroom environments, social media provides learners with continuous opportunities to engage with English in real-life contexts. Through interaction with native and non-native speakers, exposure to diverse content, and participation in online communities, learners can improve their language proficiency and develop essential communication skills. This article examines the role of social media platforms in EFL learning, highlighting their benefits, challenges, and contributions to language development.
Keywords: Social media, English as a Foreign Language, EFL, language learning, digital communication, vocabulary acquisition, language skills, online platforms.